It Gets Better: A Content Analysis of Health Behavior Theory in Anti-Bullying YouTube Videos - Lister, Cameron E; Brutsch, Elizabeth; Johnson, Amanda; Boyer, Caitlin; Hall, P. Cougar; West, Joshua H (International Journal of Health, 2013)
Bullying is a pervasive problem that affects children and adolescents of all backgrounds. Public Service Announcements (PSAs) spread through social media present a unique opportunity to reach many young people and teach skills for dealing with bullying. The purpose of this paper is to examine health behavior theory content of anti-bullying YouTube PSAs, and other YouTube videos containing anti-bullying messages. This study design comprised a content analysis for health behavior theory of anti-bullying YouTube videos. Videos were selected from www.YouTube.com using specific search terms typed into the search tool bar. Three graduate students trained in health behavior theory coded the videos. Results demonstrate that most anti-bullying YouTube videos do not incorporate health behavior theoretical constructs. Videos containing links to other websites were found to have greater inclusion of health behavior theory constructs. Theory was also positively associated with the number of views (p < .05). This paper represents the first in-depth content analysis for health behavior theoretical constructs in YouTube videos targeting bullying PSAs. Organizations should incorporate health behavior theories when developing PSAs to maximize behavioral impact, and to achieve high viewership. Overall anti-bullying videos on YouTube are ineffective in both utilizing theory and garnering views.